2017
DOI: 10.2147/ijn.s126968
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of tears following acupuncture treatment for menopausal dry eye disease by two-dimensional nano-liquid chromatography coupled with tandem mass spectrometry

Abstract: Background The purpose of this study was to investigate whether acupuncture is effective at treating dry eye disease among postmenopausal women and to identify the possible mechanisms. Methods Twenty-eight postmenopausal women with dry eye disease were randomly divided into two groups: an acupuncture plus artificial tears (AC + AT) group and an artificial tears (AT) only group. After baseline examination of clinical parameters and tear sample collection, each patient re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 31 publications
(25 reference statements)
4
57
2
Order By: Relevance
“…A total of 12 studies with 900 participants were included in this review. A majority of the studies compared manual acupuncture with AT (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). An applied form of acupuncture was used in 4 of the studies, including 1 study using silver spike point electro-therapy (35), 1 study using electroacupuncture (44) and 2 studies using combined acupuncture at the phenomaxillary ganglia with acupoints (41,42).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 12 studies with 900 participants were included in this review. A majority of the studies compared manual acupuncture with AT (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). An applied form of acupuncture was used in 4 of the studies, including 1 study using silver spike point electro-therapy (35), 1 study using electroacupuncture (44) and 2 studies using combined acupuncture at the phenomaxillary ganglia with acupoints (41,42).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Participants in the study by Zeng et al (40) were patients who experienced DED for >1 month after LASIK. Furthermore, 2 studies focused on DED in post-menopausal or peri-menopausal females (38,43). Regarding the sensation of acupoints, 4 studies reported on de-qi (soreness, numbness, sensation of heaviness or swelling) associated with the needling (35,37,40,44).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations